1995
DOI: 10.1128/jvi.69.11.6787-6796.1995
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of the adeno-associated virus (AAV) P5 promoter involves both the P5 rep binding site and the consensus ATP-binding motif of the AAV Rep68 protein

Abstract: Transcript levels from the P 5 promoter of adeno-associated virus type 2 (AAV) are negatively regulated by the AAV Rep78 and Rep68 proteins in the absence of helper virus. We have identified a Rep-responsive negative cis element of the P 5 promoter between the P 5 TATA box and transcription start site by using 5 and 3 deletions of the P 5 promoter fused to the chloramphenicol acetyltransferase gene. This element contains four imperfect GAGC repeats similar to the Rep recognition sequences (RRSs) in the AAV inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 54 publications
4
65
1
Order By: Relevance
“…2A, pIM45). This result was consistent with several reports that demonstrate Rep repression of p5 in the absence of helper virus (19,25,26). When p5CAT-transfected cells were infected with Ad, a 12.5-fold increase in CAT activity was observed ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2A, pIM45). This result was consistent with several reports that demonstrate Rep repression of p5 in the absence of helper virus (19,25,26). When p5CAT-transfected cells were infected with Ad, a 12.5-fold increase in CAT activity was observed ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Rep proteins negatively regulate p5CAT activity in the presence and absence of an Ad coinfection. As mentioned earlier, several groups have reported that in the absence of Ad helper virus, the Rep proteins negatively regulate the p5 promoter (19,25,26).In contrast, it has also been reported that in the presence of Ad, Rep can both transactivate and repress p5 transcription (3,27). To resolve Rep action at p5, expression of a CAT reporter under p5 control was used to assay promoter activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of Ad, Rep has been shown to repress both p5 and p19 transcription (21,30). Repression of p5 is mediated in part by direct binding of Rep78 or Rep68 to the p5 Rep binding element (RBE) (31,43). In the presence of helper virus, Rep78/68 transactivation of the p19 and p40 promoters is dependent on the presence of the RBEs in the p5 promoter and the terminal repeat (TR) (36,43).…”
mentioning
confidence: 99%